A Study on "Cato’s Letters" (1720-1723) and its Dissemination in the British Colonies of North America - Cueva Fernández, Ricardo (Res Publica. Revista de Historia de las Ideas Políticas, 2014)
Some “revisionist” trends in the late 1960s on the history of American emancipation suggested that existing historiography had, on the one hand, underestimated its republican features and, on the other, exaggerated John Locke’s influence. These revionists attached great importance to Cato’s Letters (1720-23), written by John Trenchard and Thomas Gordon, as an example of republican influence. However, close scrutiny of the Letters shows that that this text was, in fact, close to the thought of Locke, above all his concept of property and contractualist theory. Despite these important similarities, though, there were also key differences: to a much greater extent than Locke, its authors assumed the emergence of commercial society and emphasized freedom of religion and speech and rights of political participation. Since Trenchard and Gordon feared that the concentration of political power violated the rights of British, they advocated the strict control of the executive and the frequent Parliament elections. However, their proposed system was far from being democratic and inclusive. Trenchard and Gordon did not advance a democratic approach because, although they attached epistemic capacity to the individual under the principle of self-ownership, they did not acknowledge the same for the people as collective.
Keywords: Cato’s Letters; rights; republicanism; United States; democracy.